2011
DOI: 10.1021/am2004812
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electromagnetic, Microwave Absorbing Properties of Core–Shell Fe3O4–Poly(3, 4-ethylenedioxythiophene) Microspheres

Abstract: Highly regulated core-shell Fe(3)O(4)-poly(3, 4-ethylenedioxythiophene) (PEDOT) microspheres were successfully synthesized by a two-step method in the presence of polyvinyl alcohol (PVA) and p-toluenesulfonic acid (p-TSA). And their morphology, microstructure, electromagnetic and microwave absorbing properties were subsequently characterized. By simply adjusting the molar ratio of 3, 4-ethylenedioxythiophene (EDOT) to Fe(3)O(4) (represented by (EDOT)/(Fe(3)O(4))), the thickness of the polymer shell can be tune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(141 citation statements)
references
References 25 publications
5
136
0
Order By: Relevance
“…Here TiO 2 was taken because of its high thermal stability and moderate dielectric constant of 100 [22]. Fe 3 O 4 , a member of spinel family, was taken due to its low toxicity and great stability at high temperature [23][24]. TiO 2 coated MWCNT is well known for multipurpose applications [25][26][27][28][29].…”
mentioning
confidence: 99%
“…Here TiO 2 was taken because of its high thermal stability and moderate dielectric constant of 100 [22]. Fe 3 O 4 , a member of spinel family, was taken due to its low toxicity and great stability at high temperature [23][24]. TiO 2 coated MWCNT is well known for multipurpose applications [25][26][27][28][29].…”
mentioning
confidence: 99%
“…From the XRD profiles and SEM images, it can be concluded that the solvothermal reaction time plays a vital role on the crystal structure of TiO 2 shells and morphology of core-shell Ni/TiO 2 composites. The real permittivity (e 0 ) and real permeability (l 0 ) represent the storage ability of electromagnetic energy, while the imaginary permittivity (e 00 ) and imaginary permeability (l 00 ) are connected with the energy dissipation [20,21]. Figure 5 shows the frequency dependences of the complex permittivity (e r = e 0 -je 00 ) and permeability (l r = l 0 -jl 00 ) for the four paraffin-composites containing 70 wt% core-shell Ni/TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The relative complex permittivity (ߝ r ) and relative permeability (ߤ r ) of the absorb medium are expressed as ߝ r = ߝ ᇱ − ݆ߝ ᇱᇱ and ߤ r = ߤ ᇱ − ݆ߤ ᇱᇱ [23,24]. …”
Section: Characterizationsmentioning
confidence: 99%